Beyond the plains: deep-sea mining of polymetallic nodules on and around seamounts - Du Preez, Cherisse; Gartner, Heidi; Murdock, Sheryl; Tunnicliffe, Verena (Frontiers in Marine Science, 2025)
Deep-sea mining management, scientific research, and public discourse have largely focused on polymetallic nodule extraction from abyssal plains. However, there is growing commercial interest in nodules on and around seamounts, with exploration and testing underway in the Pacific Ocean. Increasing documentation of nodules-seamount habitats and co-occurrence with cobalt-rich ferromanganese crusts refutes the misconception that nodules occur only in abyssal plains. This also challenges the conventional management framework that separates these mineral resources into distinctly different habitats. Nodule exploitation is poised to begin soon in both environments, but under the rubric developed for abyssal plains alone. Existing and developing guidance based on the simplified resource-habitat framework is likely inadequate in addressing where nodule fields are associated with seamounts. Seamounts are ecologically significant and vulnerable features, often linked to islands as part of volcanic chains, and embedded in dynamic oceanographic systems that can amplify mining impacts. Sustainable management will require an integrated and adaptive approach, including critical reassessment of Regional Environmental Management Plans in international waters and complementary frameworks in national waters, as nodule mining moves beyond abyssal plains and onto seamounts.